Clinical results of mean GTV dose optimized robotic guided SBRT for liver metastases. Issue 1 (December 2016) - Andratschke, Nicolaus; Parys, Alan; Stadtfeld, Susanne; Wurster, Stefan; Huttenlocher, Stefan; Imhoff, Detlef; Yildirim, Müjdat; Rades, Dirk; Rödel, Claus; Dunst, Jürgen; Hildebrandt, Guido; Blanck, Oliver
Abstract Background We retrospectively evaluated the efficacy and toxicity of gross tumor volume (GTV) mean-dose-optimized and real-time motion-compensated robotic stereotactic body radiation therapy (SBRT) in the treatment of liver metastases. Methods Between March 2011 and July 2015, 52 patients were treated with SBRT for a total of 91 liver metastases (one to four metastases per patient) with a median GTV volume of 12 cc (min 1 cc, max 372 cc). The optimization of mean GTV dose was prioritized during treatment planning at the potential cost of planning target volume (PTV) coverage reduction while adhering to safe normal tissue constraints. The delivered median GTV biological effective dose (BED10 ) was 142.1 Gy10 (range, 60.2 Gy10 –165.3 Gy10 ) and the prescribed PTV BED10 ranged from 40.6 Gy10 to 112.5 Gy10 (median, 86.1 Gy10 ). We analyzed local control (LC), progression-free interval (PFI), overall survival (OS), and toxicity. Results Median follow-up was 17 months (range, 2–49 months). The 2-year actuarial LC, PFI, and OS rates were 82.1, 17.7, and 45.0 %, and the median PFI and OS were 9 and 23 months, respectively. In univariate analysis histology (p  < 0.001), PTV prescription BED10 (HR 0.95, CI 0.91–0.98, p  = 0.002) and GTV mean BED10 (HR 0.975, CI 0.954–0.996, p  = 0.011) were predictive for LC. Multivariate analysis showed that only extrahepatic disease status at time of treatment was a significant factor (p  = 0.033 andp  = 0.009, respectively) for PFI and OS. Acute nausea or fatigue grade 1 was observed in 24.1 % of the patients and only 1 patient (1.9 %) had a side effect of grade ≥ 2. Conclusions Robotic real-time motion-compensated SBRT is a safe and effective treatment for one to four liver metastases. Reducing the PTV prescription dose and keeping a high mean GTV dose allowed the reduction of toxicity while maintaining a high local control probability for the treated lesions.